Analysis of Priority Improvement in Draft Quality of Sizing Using Grey Theory in FMEA - Pujianto, Hendri; Nazar, Yunus; Mohadi, Mohadi; Gultom, Dora Virma Yolanda; Nasihardani, Dana (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Draft quality is a crucial problem in the sizing section. There were 3889 warp yarn breaks for six months. The study aims to decrease quality draft defects by applying the grey theory in the traditional FMEA. After analyzing the flow process, 41 potential causes (PC) were found from 12 potential failure modes in 7 areas. There is no significant difference in the top 5 rankings of the RPN assessment on traditional FMEA and grey theory. However, there is a slight difference in ranking on 5 PC. The first priority (RPN= 48; GR=0.588) is in the beam shaft with the creel unaligned in the beam installation (pneumatic piston not parallel). The last priority (RPN= 4; GR=0.857) is a less oiling. This research can recommend an improvement sizing process based on the proposed repairs or maintenance list, using the Grey theory in the FMEA method to decrease the weaving industry defect rate.